FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENGOBATAN TUBERKULOSIS (TB) PARU PADA PASIEN PASCA PENGOBATAN DI PUSKESMAS DINOYO KOTA MALANG - Yulinda Nur Maulidya; Endang Sri Redjeki; Erianto Fanani (Universitas Negeri Malang, 2017)
Abstract :Pulmonary tuberculosis (TB) become the most important health problem in the world. However, seeing the large number of cases of illness and death form TB, the disease can still be cured through treatment..The indicator used as a treatment evaluation is the success rate of treatment, and there are many factors that can influence the success of TB treatment. This study aims to determine the factors that can influence the success of treatment seen from aspects of age, education, income, type of treatment, knowladge, attitude of patients and the presence or absence of drug supevisor (PMO) in patients with post-treatment pulmonary TB in Puskesmas Dinoyo. This research is a case control study with 20people in case group and 10 people in the control group. Tha case group is a pulmonary TB patients who has been declared cured and the control group is a pulmonary TB patients who otherwise not cured (failed, dropped out, stopped treatment).Analysis using Kolmogorov Smirnov test and Fisher’s Exact test indicates that patients attitude and presence/absence of drug supervisor (PMO) have a significant relationship with successful treatment of pulmonary TB. While age, education, income, type of treatment and knowledge have no significant relationship with the successful treatment of pulmonary TB. Patients with a “good”attitude have an opportunity to recover 4.3 times more than patients who have “bad” or “good enough” attitudes. Patients who have drug supervisor (PMO) also tend to have an opportunity to recover 13.5 times greater than patients who do not have a drug supervisor (PMO)Abstrak :Penyakit tuberkulosis (TB) paru menjadi masalah kesehatan yang paling utama didunia. Namun, melihat banyaknya jumlah kasus kesakitan dan kematian akibat TB, penyakit ini masih dapat disembuhkan melalui pengobatan. Indikator yang digunakan sebagai evaluasi pengobatan yaitu angka keberhasilan pengobatan, dan ada banyak sekali faktor yang dapat mempengaruhi keberhasilan pengobatan TB. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang dapatmempengaruhi keberhasilan pengobatan dilihat dari aspek usia, pendidikan, penghasilan, tipe pengobatan, pengetahuan, sikap pasien serta ada/tidaknya Pengawas Minum Obat (PMO) pada pasien TB paru pasca pengobatan di Puskesmas Dinoyo. Penelitian ini berupa penelitian case control dengan 20 orang pada kelompok kasus dan 10 orang pada kelompok kontrol. Kelompok kasus merupakan pasien TB paru yang telah dinyatakan sembuh dan kelompok kontrol merupakan pasien TB paru yang dinyatakan tidak sembuh (gagal, drop out, putus berobat). Hasil analisis menggunakan uji kolmogorov smirnov dan uji fisher’s exact menunjukkan bahwa sikap pasien dan ada/tidaknya PMO memiliki hubungan yang signifikan dengan keberhasilan pengobatan TB paru. Sedangkan usia, pendidikan, penghasilan, tipe pengobatan dan pengetahuan tidak memiliki hubungan yang signifikan dengan keberhasilan pengobatan TB paru. Pasien yang memiliki sikap yang “baik” memiliki kesempatan untuk sembuh 4,3 kali lipat daripada pasien yang memiliki sikap “tidak baik” atau “cukup baik”. Pasien yang memiliki PMO juga cenderung memiliki kesempatan untuk sembuh 13,5 kali lebih besar dibandingkan pasien yang tidak memiliki PMO.Kata Kunci :tuberkulosis (TB) paru, faktor resiko, keberhasilan pengobatan